2007
DOI: 10.1159/000097938
|View full text |Cite
|
Sign up to set email alerts
|

Trait Aggression and Hostility in Recovered Alcoholics

Abstract: There is a long-recognized association between alcohol consumption and aggressive behavior. This study was designed to examine aggression in a group of socially well-adapted recovered alcoholics (RA). The question addressed was whether the treatment, together with long-term abstinence from alcohol, could reduce aggression and hostility in RA. A group of male RA (n = 64), who did not meet the DSM-IV criteria for any psychiatric or personality disorder, were recruited to the study from aftercare groups. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Higher severity of impulsivity, sensation seeking and hostility in AD subjects are concordant with the existing literature (Caces et al, 2008;Bjork et al, 2004;Lawrence et al, 2009;Fein et al, 2010;Webb et al, 1991;Ziherl et al, 2007). Similarly, presence of greater oppositional defiant, conduct, and antisocial behaviour is also quite expected (Hesselbrock et al, 1999(Hesselbrock et al, , 2003Slutske et al, 1998;Kessler et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Higher severity of impulsivity, sensation seeking and hostility in AD subjects are concordant with the existing literature (Caces et al, 2008;Bjork et al, 2004;Lawrence et al, 2009;Fein et al, 2010;Webb et al, 1991;Ziherl et al, 2007). Similarly, presence of greater oppositional defiant, conduct, and antisocial behaviour is also quite expected (Hesselbrock et al, 1999(Hesselbrock et al, , 2003Slutske et al, 1998;Kessler et al, 1997).…”
Section: Discussionsupporting
confidence: 87%
“…Notably, a recent study reported that after a 3-year abstinence period, socially well-adapted recovered alcoholics still displayed signs of hostility (Ziherl et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…This observation might lead to speculate that subjects with an important aggressive behavior are less likely to be totally abstinent during the treatment program. There is a well-recognized association between AUDs and aggressive behavior (Ziherl et al, 2007). For example, it is known that same genetic factors may be linked to both alcohol dependence and aggressive behavior (Von der Pahlen et al, 2008) and the presence of an aggressive behavior represents a marker of more severe alcohol dependence (Mann et al, 1998; Leggio and Addolorato, 2008).…”
Section: Discussionmentioning
confidence: 99%